Falta de aplicación del principio de celeridad en los procesos en materia civil, en el juzgado décimo quinto de lo civil y mercantil del cantón Pasaje, en el año 2012. - Rivera Pérez, Edwin Ramiro (2013)
The delay in processing processes in our country, makes that many times people do not demand the restitution of damage caused because during the process waste of time, economic output is generated and there is the uncertainty of administration timely justice. The Constitution of the Republic, whose principles are directly applicable, and other rules of our legal system establishes the terms in which to deal with processes of a civil nature, and the respective sanctions find regulated to punish managers d justice which delay unjustifiably them, in many cases, not to say in most of these provisions become a dead letter. Peace and harmony of a given territory, is achieved by applying a timely justice in a quick and efficient process to restore the damage that achieved in our Ecuador would be a breakthrough for the judiciary and the confidence would recover users of the same.